Gender, gendered personality traits and radical right populist voting. (May 2019) - Coffé, Hilde
Most previous research on radical right populist voting has revealed that men are substantially more likely to favour radical right parties than women. This article explores the interplay between gender, gendered personality traits – as measured by Bem's Sex Role Inventory – and radical right populist voting. To do so, it makes use of the Dutch Longitudinal Internet Studies for the Social Sciences (LISS) Household Panel (2012 and 2013; N = 4328). The Logit regression analyses reveal no noticeable effect of feminine personality traits, but a significant and positive effect of masculine personality traits on supporting the Dutch radical right party, PVV. Women are significantly less likely to support the PVV, even once gendered personality traits are controlled for, and the effects of gendered personality traits are similar among women and men.